Penataan Pedagang Kaki Lima di Sekitar Gedung Olahraga Sudiang Kota Makassar - Rosandi Sakir, Ahmad (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to describe the impact of street vendors in the area around the Sudiang Sports Building in Makassar City. The research focuses on the analysis of the impact, the perceptions of the community and vendors, as well as the role of the government in organizing street vendors in that area. The research method used is qualitative descriptive with the location of the study in Makassar City, specifically around the Sudiang sports building. The objective is to describe the arrangement of street vendors around the Sudiang Sports Building in Makassar City. Data will be collected through observation, interviews, and documentary studies. Respondents in this study include street vendors, stakeholders, and the community around the Sudiang sports building. The results of the research show that the presence of street vendors poses complex challenges, particularly in terms of aesthetic aspects, the function of the area, and economic interests. The arrangement of street vendors needs to consider economic diversity while taking into account the community's views on the aesthetics and original function of the area. In maintaining this balance, community participation and the role of the government are crucial. The government's role is felt through policies determining specific zones and supportive measures. Recommendations to maintain harmony between the economy and sports function include continued involvement of the community in decision-making regarding the arrangement of street vendors. Open dialogue among the government, vendors, and the community can serve as a platform to find solutions that accommodate the interests of all parties. Furthermore, additional efforts are needed to educate the community about the economic benefits that street vendors can bring without compromising the primary function of the area.